2018
DOI: 10.1038/s41424-018-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential metabolic effects of oral butyrate treatment in lean versus metabolic syndrome subjects

Abstract: BackgroundGut microbiota-derived short-chain fatty acids (SCFAs) have been associated with beneficial metabolic effects. However, the direct effect of oral butyrate on metabolic parameters in humans has never been studied. In this first in men pilot study, we thus treated both lean and metabolic syndrome male subjects with oral sodium butyrate and investigated the effect on metabolism.MethodsHealthy lean males (n = 9) and metabolic syndrome males (n = 10) were treated with oral 4 g of sodium butyrate daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 48 publications
(63 reference statements)
8
146
1
1
Order By: Relevance
“…On estimating the role of Odoribacter in insulin sensitivity, it was found that Odoribacter produced butyrate 34 . Oral butyrate treatment was reported to improve insulin sensitivity in healthy lean men 35 . In the present study, there was no difference in the fecal butyrate concentration between the two groups, and thus butyrate might not have been the main contributor to the differences in the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…On estimating the role of Odoribacter in insulin sensitivity, it was found that Odoribacter produced butyrate 34 . Oral butyrate treatment was reported to improve insulin sensitivity in healthy lean men 35 . In the present study, there was no difference in the fecal butyrate concentration between the two groups, and thus butyrate might not have been the main contributor to the differences in the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, blood lipids (triglycerides, cholesterol, and total fatty acids) were decreased. However, when oral butyrate was given for 4 weeks to human subjects, only lean subjects showed an increase in insulin sensitivity whereas obese insulin resistant subjects did not show any effect …”
Section: Methodsmentioning
confidence: 93%
“…However, when oral butyrate was given for 4 weeks to human subjects, only lean subjects showed an increase in insulin sensitivity whereas obese insulin resistant subjects did not show any effect. 81 One of the butyrate producing bacteria of particular interest for the use as probiotic is the anaerobic, Gram-positive E hallii, belong-…”
Section: Probioticsmentioning
confidence: 99%
“…Nevertheless, it remains uncertain whether changes in butyrate caused this improvement in insulin sensitivity, as the study was not designed to evaluate a causal link [70]. Noteworthy, four weeks of oral butyrate supplementation to metabolic syndrome subjects showed no effect on insulin sensitivity [71]. The absence of effect could be due to the oral ingestion of butyrate.…”
Section: Microbiota-derived Metabolites Linked To Cmdmentioning
confidence: 99%